An Efficient Amphiphilic‐Type Triphenylamine‐Based Organic Hole Transport Material for High‐Performance and Ambient‐Stable Dopant‐Free Perovskite and Organic Solar Cells. Issue 24 (14th April 2018) - Reddy, Saripally Sudhaker; Park, Ho‐Yeol; Kwon, Haeun; Shin, Jongmoon; Kim, Chang‐Su; Song, Myungkwan; Jin, Sung‐Ho
Abstract: A new set of simply structured triphenylamine‐based small molecules are synthesized and evaluated as dopant‐free hole transporting materials (HTMs) for high‐performance perovskite solar cells (PSCs) and bulk heterojunction inverted organic solar cells (BHJ IOSCs). Surprisingly, the new amphiphilic‐type HTM‐1 (with internal hydrophilic groups and peripheral hydrophobic alkyl tails) showed better compatibility and performance than the actual target molecule, that is, HTM‐2 in PSCs and BHJ IOSCs. Importantly, the HTM‐1‐based dopant‐free PSCs and BHJ IOSCs exhibited high power conversion efficiencies (PCEs) of 11.45 % and 8.34 %, respectively. These performances are superior and comparable to those of standard HTMs Spiro‐OMeTAD (2, 2′, 7, 7′‐tetrakis( N, N ‐di‐ p ‐methoxyphenylamine)‐9, 9′‐spirobifluorene) and PEDOT:PSS (poly(3, 4‐ethylenedioxythiophene)/polystyrene sulfonate) in PSCs and BHJ IOSCs, respectively. The enhanced device performance of the HTM‐1‐based PSCs is ascribed to its strong affinity towards the perovskite, properly aligned energy levels with respect to the perovskite valence band, and excellent hole transporting behavior. In addition, the well‐organized energy levels of the HTMs showed excellent compatibility in BHJ IOSCs. The new amphiphilic‐type HTM‐based photovoltaic devices also showed long‐term air stability over 700 h. These promising results offer new and unexpected prospects for engineering the interface between the photoactive material and HTMs in PSCs and BHJ IOSCs. Abstract : A new amphiphilic‐type hole transport material HTM‐1 (with internal hydrophilic groups and peripheral hydrophobic alkyl tails) shows better compatibility and performance than the actual target molecule, that is, HTM‐2 and standard HTMs Spiro‐OMeTAD and PEDOT:PSS in perovskite solar cells and bulk heterojunction inverted organic solar cells.